The role of mechanosensitive ion channels in the gastrointestinal tract - Yang, Haoyu; Hou, Chaofeng; Xiao, Weidong; Qiu, Yuan (Frontiers in Physiology, 2022)
Mechanosensation is essential for normal gastrointestinal (GI) function, and abnormalities in mechanosensation are associated with GI disorders. There are several mechanosensitive ion channels In the GI tract, namely transient receptor potential (TRP), piezo, two-pore domain potassium (K2p), and voltage-gated ion channels. These channels are located in many mechanosensitive intestinal cell types, namely enterochromaffin (EC) epithelial cells, interstitial cells of Cajal (ICC), smooth muscle cells (SMCs), and intrinsic and extrinsic enteric neurons. In these cells, mechanosensitive ion channels can alter transmembrane ion currents in response to mechanical forces, through a process known as mechanoelectrical coupling. Furthermore, abnormal mechanical stimuli are often associated with a variety of GI tract disorders, including irritable bowel syndrome (IBS), GI tumors, and Hirschsprung disease (HD). Mechanical stimuli could therefore provide a new perspective for the treatment of GI diseases. This review aims to highlight recent research advances regarding the function of mechanical stimulation in the GI tract. Moreover, this review outlines the potential role of mechanical stimulation in related diseases, while describing the current understanding of GI-mechanical stimulation interactions.